Komunikasi Ideal Pada Masyarakat Perkotaan Konsep Metode-Metode Islam - Anggun Nopita; Efri Yansyah; Rico Agu Mario; Solimin Solimin (STAI Bumi Silampari, 2021)
Methods of Communication Da'wah in urban communities where there are many multicultural communities of different ethnicities and cultures need good communication, especially in religion. In realizing the extent to which the implementation of Islamic society in Taba Jemekeh Village, Lubuklinggau, knowing the methods used in da'wah communication in realizing an Islamic society, knowing the Islamic Community in Taba Jemekeh Lubuklinggau Village, the role of da'wah communication in realizing an Islamic society. This research is descriptive qualitative, which is a research that is intended to reveal an empirical fact scientifically objectively based on scientific logic, procedures, and supported by strong methodologies and theories in accordance with known scientific disciplines.